Fruit firmness, superficial damage, and location modulate infestation by Drosophila suzukii and Zaprionus indianus: the case of guava in Veracruz, Mexico. Issue 1 (9th December 2016) - Lasa, Rodrigo; Tadeo, Eduardo; Dinorín, Luis A.; Lima, Itzel; Williams, Trevor
Abstract: The exotic pestiferous flies Drosophila suzukii (Matsumura) and Zaprionus indianus Gupta (Diptera: Drosophilidae) were recently identified in traps used for monitoring tephritid pests of guava, Psidium guajava L. (Myrtaceae), in Veracruz, Mexico. To determine whether both drosophilids were infesting guava, a previously unreported host, samples were taken from fruits on trees and fallen fruits on the ground. Overall, 74 and 36% of visually intact fruits attached to the tree were infested by D. suzukii and Z. indianus, respectively. Under laboratory conditions, small artificial punctures on the surface of ripe guavas did not result in increased oviposition by D. suzukii compared to undamaged fruit, whereas Z. indianus almost completely avoided oviposition, or were not capable of developing in fruit. Females of D. suzukii were capable of ovipositing in early ripe guavas in laboratory tests (23% of fruits were used for oviposition), although a high penetration force is required to pierce fruit (mean ± SEM = 89.0 ± 3.0 cN). Fully ripe and overripe guavas were softer (52.2–53.5 cN penetration force) and were more frequently infested (ca. 60% infestation). Numbers of females that developed in guavas were not influenced by ripeness/firmness, whereas male development was reduced in early ripe fruit compared to ripe and overripe fruit. In laboratory choice experiments with crushed fruits, D. suzukii adults were equally attracted to guava and blueberry, independent of gender and age. However, raspberry was more attractive than guava. This study demonstrates that D. suzukii is attracted to guava, is capable of ovipositing in fruit and, under field conditions, is more abundant in fruits still attached to the tree compared to fallen fruit that remain intact. In contrast, Z. indianus was not capable of developing in intact guavas and, although present in fruits attached to the tree, was most abundant in fallen damaged fruits.